Association of gastroesophageal reflux disease and laryngeal cancer - Mursalin M. Anis (KeAi Communications Co., Ltd., 2018)
Objective: Studies examining the association of reflux disease with the risk of developing laryngeal cancer have both proven and disproven the null hypothesis. Methods: This retrospective case–control study examines the association of reflux in two populations exposed to similar risk factors, including tobacco, to the extent that end-organ malignant transformation has occurred. After IRB approval was obtained, a search of our hospital's cancer center's database was performed from 2000 to 2013. A retrospective chart review was then performed and the prevalence of gastroesophageal reflux disease among patients with laryngeal cancer (n = 290) was determined. It was then compared to the prevalence of gastroesophageal reflux disease among patients presenting with lung cancer (n = 2440) during the same time period. A multivariate logistic regression was performed to determine the association of reflux with laryngeal cancer. Results: Taking into consideration tobacco use, there was a strong association between male gender and occurrence of laryngeal cancer as opposed to lung cancer (OR = 3.30; 95% CI 2.53–4.36, P < 0.001). There was a modest association between reflux and laryngeal cancer (OR = 1.65; 95% CI 1.19–2.25, P = 0.003). However, there was no association between reflux and the propensity for carcinoma in specific laryngeal subsites (P = 0.47). Conclusions: In this study examining a heterogeneous population with end-organ malignancy there was a modest association between reflux and laryngeal cancer. Further research is necessary to determine the biologic relevance of this finding. Keywords: Laryngopharyngeal reflux, GERD, Extraesophageal reflux, Laryngeal cancer, Lung cancer